Highly N2-Selective Activated Carbon-Supported Pt-In Catalysts for the Reduction of Nitrites in Water - Soares, Olívia Salomé G. P.; Jardim, Erika O.; Ramos-Fernandez, Enrique V.; Villora-Picó, Juan J.; Pastor-Blas, M. Mercedes; Silvestre-Albero, Joaquín; Órfão, José J. M.; Pereira, Manuel Fernando R.; Sepúlveda-Escribano, Antonio (Frontiers in Chemistry, 2021)
The catalytic reduction of nitrites over Pt-In catalysts supported on activated carbon has been studied in a semi-batch reactor, at room temperature and atmospheric pressure, and using hydrogen as the reducing agent. The influence of the indium content on the activity and selectivity was evaluated. Monometallic Pt catalysts are very active for nitrite reduction, but the addition of up to 1 wt% of indium significantly increases the nitrogen selectivity from 0 to 96%. The decrease in the accessible noble metal surface area reduces the amount of hydrogen available at the catalyst surface, this favoring the combination of nitrogen-containing intermediate molecules to promote the formation of N2 instead of being deeply hydrogenated into NH4+. Several activated carbon-supported Pt-In catalysts, activated under different calcination and reduction temperatures, have been also evaluated in nitrite reduction. The catalyst calcined and reduced at 400°C showed the best performance considering both the activity and the selectivity to nitrogen. This enhanced selectivity is ascribed to the formation of Pt-In alloy. The electronic properties of Pt change upon alloy formation, as it is demonstrated by XPS.